Effectiveness of flexible endoscopy in the management of upper gastrointestinal tract foreign bodies at a tertiary hospital of western Nepal - Chaudhary, Shatdal; Khatri, Prabin; Shrestha, Suresh (Journal of Chitwan Medical College, 2020)
Background: Foreign body ingestions are some of the most challenging clinical scenarios faced by gastrointestinal endoscopists. The commonly ingested foreign bodies are coins, toys, and batteries in children whereas bone or meat boluses are common in adults. The present study was carried out to study the clinical profile of patients presenting with foreign body in the upper gastrointestinal tract and effectiveness of endoscopy as a therapeutic tool in its management. Methods: A descriptive cross-sectional study was carried out in the endoscopy unit of Universal College of Medical Sciences, Bhairahawa, Nepal from Jan 2015 to Dec 2018. All patients who underwent endoscopy with suspicion of ingestion of foreign body in the upper gastrointestinal tract were enrolled in this study. Foreign body was removed with appropriate endoscopic tools. Results: Sixty-four patients were enrolled in the present study with mean age of 34.78±21.84 years. There were 42.19% (n=27) males with female preponderance (57.37%, n=37). Retrosternal discomfort with dysphagia was the most common presentations seen in 68.75% (n=44) patients. The most common site for foreign body impaction was lower oesophagus (53.13%). Three most common foreign bodies encountered were meat bone, meat balls and coins respectively. Endoscopic management was successful in 59 (92.19%) patients. Conclusions: Foreign body ingestion is commonly seen in children and young adults with female predominance. Most common upper gastrointestinal foreign bodies are related to food bolus impaction with animal bone or meat. Therapeutic endoscopy is a safe and effective method for removing foreign body from upper gastrointestinal tract.